Action, Intersubjectivity and Narrative Identity Essays on Critical Hermeneutics - Busacchi, Vinicio (Cambridge Scholars Publishing, 2019)
The book reconsiders Paul Ricoeur's speculative research from the perspective of a critical hermeneutics understood as a general methodology which is able to work at an interdisciplinary level. The specialisation of sciences results in a differentiation of knowledge that determines advancement, while also provoking a great increase of complexity and fragmentation. As such, among the human sciences, some problematic disciplines, like psychoanalysis, sociology and history, have not yet found a unified methodological and epistemological structure. This book argues that critical hermeneutics may w.